Cultural beliefs and practices of women influencing home births in rural Northern Ghana - Adatara P; Strumpher J; Ricks E; Mwini-Nyaledzigbor PP (Dove Medical Press, 2019)
Peter Adatara,1 Johanita Strumpher,2 Esmeralda Ricks,2 Prudence Portia Mwini-Nyaledzigbor11Department of Nursing, University of Health and Allied Sciences, Ho, Ghana; 2Department of Nursing, Nelson Mandela University, Port Elizabeth, South AfricaBackground: One of the maternal health care strategies identified by the World Health Organization as being crucial for saving lives of pregnant women, which also serves as an indicator for progress in reducing maternal mortality, is the provision and utilization of skilled birth care. Despite the importance of skilled birth care in preventing maternal morbidity and mortality, many women continue to give birth at home without the assistance of skilled birth attendants in rural communities of Ghana.Purpose: The purpose of this study was to explore the cultural beliefs that potentially influenced the choice of home births among rural women in Ghana.Methods: A qualitative approach was utilized to conduct this study. Twenty participants who delivered at home were purposefully selected and interviewed individually. Semistructured interviews were used to explore the cultural belief patterns that potentially influenced the choice of home births among women in rural Ghana. Thematic analysis approach was used to analyze the data.Results: Four major themes emerging from the data analysis which influenced rural women’s decision to give birth at home are namely: opportunity to access psychological support through family members, opportunity to access culturally acceptable food, opportunity to adopt a birthing position of choice, and opportunity for safe and culturally accepted disposal of placenta.Conclusion: This study concluded that the cultural beliefs held by these women greatly affected their decision to deliver at home. Hence, there is a need for health care managers to facilitate collaborative practices between the skilled birth attendants and traditional birth attendants. This is because this approach could enhance the integration of the cultural beliefs and practices of women in the orthodox health care delivery system to facilitate the utilization of skilled birth care.Keywords: cultural beliefs, perceptions, laboring women, home birth care, skilled birth attendants